The macroeconomic cost of climate volatility - Piergiorgio Alessandri; Haroon Mumtaz (Queen Mary University of London, School of Economics and Finance, 2021)
We study the impact of climate volatility on economic growth exploiting data on 133 countries between 1960 and 2005. We show that the conditional (ex ante) volatility of annual temperatures increased steadily over time, rendering climate conditions less predictable across countries, with important implications for growth. Controlling for concomitant changes in temperatures, a +1oC increase in temperature volatility causes on average a 0.9 per cent decline in GDP growth and a 1.3 per cent increase in the volatility of GDP. Unlike changes in average temperatures, changes in temperature volatility affect both rich and poor countries.
Keywords: C32; E32; F34; 330; temperature volatility; economic growth; panel VAR